1997
DOI: 10.1136/vr.140.5.116
|View full text |Cite
|
Sign up to set email alerts
|

Effects on calves less than one month old of feeding or not feeding them during road transport of up to 24 hours

Abstract: Two trials, each involving 56 calves less than one month old, demonstrated that the responses of calves to food and water deprivation during 24 hours of transport were similar to those observed in older cattle and lambs. There was increasing utilisation of body reserves and a measurable increase in dehydration, coupled with an increased loss of liveweight. Feeding 1 litre of glucose/electrolyte solution at eight-hour intervals did reduce the effects of food and water deprivation, but it is suggested that the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
89
2
5

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(106 citation statements)
references
References 5 publications
(7 reference statements)
10
89
2
5
Order By: Relevance
“…The observed concentrations of post-mortem catecholamines in steers that relied on natural pasture alone were higher than those that were reported by Ndlovu et al (2008) and Muchenje et al (2009). The variation could be due to the differences in age-related responses to pre-slaughter stress (Knowles et al, 1997). Nguni steers in this study were 3 months older at slaughter compared with those used by Ndlovu et al (2008) and Muchenje et al (2009).…”
Section: Discussioncontrasting
confidence: 69%
“…The observed concentrations of post-mortem catecholamines in steers that relied on natural pasture alone were higher than those that were reported by Ndlovu et al (2008) and Muchenje et al (2009). The variation could be due to the differences in age-related responses to pre-slaughter stress (Knowles et al, 1997). Nguni steers in this study were 3 months older at slaughter compared with those used by Ndlovu et al (2008) and Muchenje et al (2009).…”
Section: Discussioncontrasting
confidence: 69%
“…Lack of stress responses in some of the investigations mentioned above is therefore not evidence that transport is not stressful for calves in this age group. There are, however, investigations that do find effects (Grigor et al, 2001), whereas others do not find effects (Knowles et al, 1997) of transport on typical physiological measures of stress such as plasma cortisol concentration. These divergent results may be due to differences in the developmental stage of the calves, highlighting the difficulties in using these measures to assess welfare in young animals.…”
Section: Calvesmentioning
confidence: 93%
“…Swanson and Morrow-Tesch (2001) reported that young cattle exhibit increased mortality and morbidity during transportation compared with older cattle due to a lack of exposure to the new environment and a naive immune system. In contrast, Knowles et al (1997) found a negative correlation between age at transport and mortality. Although the BRDC is a multifactorial condition, it is arguably of greatest importance to gain a better understanding of the mechanisms that drive the compromised immune function that first allows invasion of opportunistic pathogens (Caswell, 2014).…”
Section: Introductionmentioning
confidence: 69%